Gambaran Pola Pemberian Makan Dan Pola Asuh Pada Balita Stunting - Natalia, Lia; Yuwansyah, Yeti; Andini, Andini (Akademi Kebidanan Bunga Husada Samarinda, 2022)
Stunting is a condition of impaired growth and development in children due to chronic malnutrition so that children have low height-for-age. Under-five children with stunting are thise with a z-score of less than -2SD/standard deviation (stunted) and less than -3SD (severely stunted). This study aims to describe the feeding and parenting patterns toward under-five children with stunting.This was a quantitative descriptive study. The populations in this study were mothers who had under-five children with stunting as many as 596 women and the samples were 86 women who were selected using purposive sampling technique. The data collection instrument was a questionnaire. Univariate data analysis was performed through frequency distribution. The results of study showed that a small proportion (15.1%) of under-five children with stunting were in the very short category, less than half (48.8%) of respondents performed inappropriate feeding pattern for under-five children with stunting and less than half (47.7%) of respondents performed ignorance in parenting pattern towards under-five children with stunting. For healthcare workers, it is necessary to increase counseling effort to mothers of under-five children about stunting along with its prevention, motivate mothers of under-five children to provide nutritional food and perform appropriate parenting pattern for their children. Furthermore, it is necessary to optimize the role of cadres and integrated healthcare post activities to monitor the development of under-five children continually. Mothers of under-five children are expected to actively participate in integrated healthcare post activities, attend counseling events and be diligent in seeking information either through the media or by asking to healthcare workers regarding stunting and how to prevent it. In addition, mothers of under-five children should manage time to care for their children so as to have optimal growth and development.